2006
DOI: 10.1016/j.compositesa.2005.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of glass fibres used in automotive industry for SMC body panels

Abstract: Advances in surface quality and a better understanding of the formation mechanisms of surface defects are required for SMC applications as body panels in the automotive industry. This study is focused on the influence of the material formulation and SMC process on the surface quality, which is probably conditioned by the interactions between the paste and the fibres. The main parameters are: (i) the amount of sizing applied on fibres, (ii) the type of antistatic agent and its deposit method and (iii) the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A-SMCs are provided by Plastic Omnium Auto Exterior and are processed by thermocompression [7]. These composites are commonly used as a substitute for steels in structural automotive components because of their high strength-to-weight ratio [31,32]. A recent study [7] have demonstrated their high stiffness and strength together with low density compared to metals which make them suitable materials for crashworthy small weight automotive structures.…”
Section: Introductionmentioning
confidence: 99%
“…A-SMCs are provided by Plastic Omnium Auto Exterior and are processed by thermocompression [7]. These composites are commonly used as a substitute for steels in structural automotive components because of their high strength-to-weight ratio [31,32]. A recent study [7] have demonstrated their high stiffness and strength together with low density compared to metals which make them suitable materials for crashworthy small weight automotive structures.…”
Section: Introductionmentioning
confidence: 99%
“…Interphases with gradual or monotonic change of mechanical properties and composition rather than homogeneous properties are highly expected, since in such case mechanical stresses can be efficiently transferred from matrix to reinforcement and the concentration of mechanical and thermomechanical stresses at this area can be greatly avoided [5]. Recent progresses in mechanical characterisation on interphases in combination with adhesion strength measurement and real composite mechanical tests indicated the presence of an interphase with mechanical property gradients leading to high mechanical properties [6][7][8][9][10][11]. As there is a steadily increasing interest in the use of thermoplastic composites in different fields, such as construction, automotive industries and aeronautic industries, in the field of GF reinforced thermoplastic composites various strategies have been developed in order to tailor the interphase characteristics, which mainly focused on the modification of GF surface or matrix, aiming at enhancing the GF-matrix adhesion strength, such as by enhancing GF-matrix compatibility, mechanical interlocking, and acid-base interaction [1][2][3][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…For real reinforcements sized with the complete sizing formulation, it was proposed that silane coupling agent enriches on the sizing/GF interface, while the polymeric film former predominates on the sizing/ air interface, hence polymeric film former and polysiloxane network form an interpenetrating network (IPN) with gradual change of chemical composition from silane coupling agent dominated phase to polymeric film former enriched phase [29,35]. Literature addressing the formation of interphase dependence of sizing structure based on the complete sizing package is very limited [9][10][11]36]. In this study, silane coupling agent and polymeric film former were applied sequentially on as-spun GF at different stages, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The PCA matrix was based on peak lists for the positive ion mass spectra of the four samples, three spectra for each. Each peak of significant intensity in the mass range of 0–300 m/z was selected, including those characteristic of E‐glass and carbon fiber47–49 Table 6 outlines an abbreviated peak list for all composite samples illustrating the mass resolution of ToF‐SIMS along with the subtle differences between spectra.…”
Section: Tof‐sims and Pcamentioning
confidence: 99%